Sp1 Targeted PARP1 Inhibition Protects Cardiomyocytes From Myocardial Ischemia–Reperfusion Injury via Downregulation of Autophagy - Xu, Yifeng; Wang, Boqian; Liu, Xiaoxiao; Deng, Yunfei; Zhu, Yanqi; Zhu, Feng; Liang, Yanyan; Li, Hongli (Frontiers in Cell and Developmental Biology, 2021)
Myocardial ischemia–reperfusion injury (MIRI), characterized by post-ischemic cardiomyocytes death and reperfusion myocardial damage, is a lethal yet unresolved complication in the treatment of acute myocardial infarction (AMI). Previous studies have demonstrated that poly(ADP-ribose) polymerase-1 (PARP1) participates in the progression of various cardiovascular diseases, and various reports have proved that PARP1 can be a therapeutic target in these diseases, but whether it plays a role in MIRI is still unknown. Therefore, in this study, we aimed to explore the role and mechanism of PARP1 in the development of MIRI. Firstly, we demonstrated that PARP1 was activated during MIRI-induced myocardial autophagy in vitro. Moreover, PARP1 inhibition protected cardiomyocytes from MIRI through the inhibition of autophagy. Next, we discovered that specificity protein1 (Sp1), as a transcription factor of PARP1, regulates its target gene PARP1 through binding to its target gene promoter during transcription. Furthermore, silencing Sp1 protected cardiomyocytes from MIRI via the inhibition of PARP1. Finally, the functions and mechanisms of PARP1 in the development of MIRI were also verified in vivo with SD rats model. Based on these findings, we concluded that PARP1 inhibition protects cardiomyocytes from MIRI through the inhibition of autophagy, which is targeted by Sp1 suppression. Therefore, the utilization of PARP1 exhibits great therapeutic potential for MIRI treatment in future.